The charred plant remains from Baleshare and Hornish Point (Scottish Historical and Archaeological Internet Reports, 2003)
Crops were mainly barley with a little wheat. Wild species included sedges, heath grass, knotgrass, brassicas/charclock, heather ling or heath, dock and chickweed.